Complex psychotherapeutic and psycho-social assistance for schizophrenia patients - Lozan, I. Yu. (Journal of Education, Health and Sport, 2020)
Schizophrenia is a global health burden with a high economic cost to health systems and an independent risk factor for decreased quality of life. The objective: to develop comprehensive measures of psychotherapy and psychosocial rehabilitation taking into account the gender characteristics of paranoid schizophrenia patients, and evaluate their effectiveness. Methods: analysis of theoretical heritage, socio-demographic, clinical and psychopathological. Results: The system of psychotherapeutic interventions included individual and group work. At the outpatient stage a program directed to restore adaptive skills: household, social, communication was used. In the process of social skills training the principles of social learning were used. At the stage of active therapy normalization of behavior, elimination of psychomotor arousal, reduction of psychotic symptoms severity; partial resumption of criticism was the ultimate aim. At the stage of stabilizing antipsychotic therapy - reverse development of residual productive symptoms and reduction of negative, affective and cognitive symptoms, increasing of social adaptation; at the stage of supportive (preventive) antipsychotic therapy - maintaining the optimal level of social functioning of the patient. Conclusion: The use of complex measures of psychotherapy and psychosocial rehabilitation developed allowed to level psychotic manifestations and form a stable remission, reduce maladaptive manifestations in psycho-emotional and cognitive spheres, improve social functioning of a patient and his family.